Calvin for the Third Millennium - Mol, Hans (ANU Press, 2008)
This work is a series of sermons produced by Emeritus Professor Hans Mol, and based on Biblical texts, the Commentaries of John Calvin on these texts, and on Calvin's Institutes of the Christian Religion. Mol is Australia's pre-eminent scholar in the sociology of religion, particularly in Australia. His 1971 volume, Religion in Australia, was the first attempt at statistical analysis of religion in Australia, which was also internationally significant. Parallel to Mol's interest in the sociology of religion has been his interest in Calvin. Indeed the theological basis of his life has been as a Calvinist. Here in this volume he brings both of these interests together. His sermons, preached over the years in Canberra, seek to apply the teachings of Calvin to a world-view in which the scientific study of religion, and indeed the wider study of sociology, are of central significance. In these sermons, he succeeds considerably in this. The volume is a substantial contribution to scholarship, in that the combination of these two factors has only rarely been attempted. Thus, the volume has originality and will have enduring value. It is especially appropriate that it should be published at this time, in preparation for the 500th Anniversary of Calvin's birth (1509-2009).